A Model of Heterosexual Adaptive Relationship Functioning in South Africa: Implications for HIV Prevention Interventions. Issue 4 (2nd October 2018) - Belus, Jennifer M.; Baucom, Donald H.; Carney, Tara; Carrino, Emily; Wechsberg, Wendee M.
Abstract: Objectives: Couple-based HIV prevention efforts are an important HIV prevention strategy in South Africa but there is a lack of understanding as to what constitutes healthy relationships in South African sociodisadvantaged communities. Methods: To address this, 8 focus group discussions were conducted with 27 men and 23 Black African women living in a large disadvantaged community in Cape Town, South Africa. Results: A model of adaptive relationship functioning is put forth, which involves four primary relationship components that emerged as central to healthy relationships: active relationship building, emotional support/display, communication, and problem-solving. Conclusions: The results of this study can inform couple-based HIV prevention efforts.